Transdermal anastrozole patch formulation and in vitro release study - A. Alwan, Laila; Abd Alhammid, Shaimaa Nazar (Pharmakeftiki, 2025)
Anastrozole is commonly prescribed to postmenopausal women with hormone-sensitive breast cancer; however, its severe side effects – often dependent on dosage – are frequently linked to the standard oral formulation. A sustained-release transdermal delivery system may offer a means of mitigating these adverse effects. In this study, transdermal patches containing anastrozole were developed, and the influence of polymer composition on the drug’s in vitro release profile was evaluated. Polyethylene glycol 400 (PEG 400) served as a plasticizer, with varying ratios of hydrophobic to hydrophilic polymers: Eudragit L-100 and hydroxypropyl methylcellulose (HPMC), respectively. The formulations were assessed for their physicochemical properties and their in vitro drug release in phosphate-buffered solution (pH 7.4) at 32.0°C ± 1.0°C. Among these, the formulation containing a 7:3 Eudragit L-100 to HPMC ratio was selected, as its release kinetics conformed to the Higuchi model, thereby suggesting diffusion as the predominant mechanism of sustained drug release.